EKSISTENSI TOKOH DALAM NOVEL KUBAH KARYA AHMAD TOHARI - Nurul Resky; Syafrial '; Abdul Razak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study discusses the existence of each character in the novel Kubah by Ahmad Tohari. In this study, there is a problem formulation that examines how the existence of a character in the novel Kubah by Ahmad Tohari and aims to describe the existence of a character in the novel Dome by Ahmad Tohari. The source of data that became the object of this research is the novel Dome by Ahmad Tohari. The research data that writers look for in the form of sentences and quotations of dialogue related to the existence of characters who experienced three stages of existence, namely the aesthetic stage, ethical stage and religious stage. The research method used is a qualitative method that describes the description data. Technique of collecting data in this research is literature study. While the analysis technique used is reducing data, presenting the data and drawing the final conclusion. The data of this study amounted to 53 consisting of 13 characters, each character experienced three stages of existence that is the existence of the aesthetic stage, the existence of the ethical stage and the existence of the religious stage. The details of 53 data are as follows, at the aesthetic stage found 13 data, the existence of the ethical stage found 22 data, and the existence of the religious stage found 18 data.Keywords: Figures of exIstence, the Dome of the Novel by Ahmad Tohari.